Evaluation of Employee Mental Workload Using the Rating Scale Mental Effort and KAUPK2 Method in the Production Process of Spoon Making PT. VRIZ - Fais, Moh. Ainul; Deviyanti, I Gusti Ayu Sri; Tjandra, Suhatati; Mohamad, Silvana; Lapai, Yolanda; Syahrir H, Muhammad (Universitas Teuku Umar, 2024)
Ergonomics is an approach that makes humans the main actors in the smooth running of the work system. PT. VRIZ is a company that produces stainless steel spoons. The manufacture of spoon products has 8 stages of the process with one employee working at any time and not allowed to stop before break time, the working hours that apply to this company are 7 working hours with 1 hour of rest. Static work has the potential to be easily bored, saturated and sleepy. This study aims to minimize the risky process flow taken in evaluating employee mental workload, analyzing the results of the two methods used, and providing recommendations for improvements in the workplace. With a better understanding of employee mental workload, PT. VRIZ can achieve higher levels of productivity and create a healthier and more sustainable work environment. The stages in this study use the RSME and KAUPK2 methods in data collection, this approach has a tool in the form of a questionnaire that must be filled out by the object or employee. The data obtained will be an early indication to provide improvements to the work system to reduce the impact of work fatigue. The Mental Effort Rating Scale questionnaire is one method of measuring mental workload by referring to the effort expended, while KAUPK2 is one method of measuring worker fatigue. The results of the Mental Effort Rating Scale show an average value of mental load of 115 (the effort expended is very large) and employee work fatigue using KAUPK2 shows the most dominant attributes felt by 8 employees, namely being reluctant to look others in the eye, being reluctant to work diligently and feeling tired all over the body.